Effect of once weekly folic acid supplementation on erythrocyte folate concentrations in women to determine potential to prevent neural tube defects: a randomised controlled dose-finding trial in Malaysia - Samson, Kaitlyn L. I .; Loh, Su Peng; Khor, Geok Lin; Mohd Shariff, Zalilah; Yelland, Lisa N.; Leemaqz, Shalem; Makrides, Maria; Hutcheon, Jennifer A.; Sulistyoningrum, Dian C.; Yu, Jessica J.; Roche, Marion L.; De-Regil, Luz Maria; et al. (BMJ Publishing Group, 2020)
Introduction Folic acid (0.4 mg) taken prior to and during early pregnancy reduces the risk of neural tube defects (NTDs). Because these birth defects occur early in pregnancy, before women may know they are pregnant, many countries have mandated the addition of folic acid to food staples. In countries where fortification is not possible, and weekly iron folic acid programmes exist to reduce anaemia, the WHO recommends that 2.8 mg (7×0.4 mg) folic acid be given instead of the current weekly practice of 0.4 mg. Currently, there is a lack of evidence to support if the 2.8 mg folic acid per week dose is sufficient to raise erythrocyte folate concentrations to a level associated with a reduced risk of a NTD-affected pregnancy. We aim to conduct a three-arm randomised controlled trial to determine the effect of weekly folic acid with iron on erythrocyte folate, a biomarker of NTD risk. Methods and analysis We will recruit non-pregnant women (n=300; 18–45 years) from Selangor, Malaysia. Women will be randomised to receive either 2.8, 0.4 or 0.0 (placebo) mg folic acid with 60 mg iron weekly for 16 weeks, followed by a 4-week washout period. The primary outcome will be erythrocyte folate concentration at 16 weeks and the mean concentration will be compared between randomised treatment groups (intention-to-treat) using a linear regression model adjusting for the baseline measure. Ethics and dissemination Ethical approval was obtained from the University of British Columbia (H18-00768) and Universiti Putra Malaysia (JKEUPM-2018-255). The results of this trial will be presented at scientific conferences and published in peer-reviewed journals.